2015 IEEE Information Theory Workshop - Fall (ITW) 2015
DOI: 10.1109/itwf.2015.7360752
|View full text |Cite
|
Sign up to set email alerts
|

Protograph design for spatially-coupled codes to attain an arbitrary diversity order

Abstract: This work focuses on the design of SC-LDPC codes for transmission over non-ergodic, block-fading channels. Our main contribution is an algorithm, allowing to start from a (J, K)-regular, uncoupled LDPC ensemble, from which one can recursively build up a protograph-based SC-LDPC ensemble having any target diversity order d. The diversity order is achieved assuming a low-complexity iterative decoding algorithm. The increase of d comes at the cost of increasing the memory constraint (i.e., the coupling parameter)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Recently, in [16], [17], it has been shown that some welldesigned protograph-based LDPC codes can increase the diversity order of block fading channels and are thus also good candidates for block erasure channels. The tradeoff with these constructions is, however, that they require large syndrome former memories if the burst length becomes large.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in [16], [17], it has been shown that some welldesigned protograph-based LDPC codes can increase the diversity order of block fading channels and are thus also good candidates for block erasure channels. The tradeoff with these constructions is, however, that they require large syndrome former memories if the burst length becomes large.…”
Section: Introductionmentioning
confidence: 99%
“…in an increased required window length and thus also in an increased complexity. Recently, it has been shown that protograph-based LDPC codes can increase the diversity order of block fading channels and are thus good candidates for block erasure channels [7], [8]; however, they require large syndrome former memories if the burst length becomes large. Closely related structures based on protographs have been proposed in [9] which spatially couple the special class of root-check LDPC codes [10] to improve the finite length performance and thresholds.…”
Section: Introductionmentioning
confidence: 99%